(untitled) (Khairulummah, 2022)
The land of Lucky Marwat gave birth to great commentators, muhaddithians, jurists, writers, scholars with great political and social services. Chagaye and this series is still continuing in the same way. Some of these scholars are those whose mentions have graced the pages of history, while the majority are those scholars whose mentions in history are silent and despite their scholarly glory and religious, political and social services, history has ignored them. Maulana Jamshed has done research in order to present the services of these forgotten men of history to the Muslim Ummah, in which the services of more than 40 distinguished scholars have been reviewed in one column. However, this work of his is brief, although there are some of these personalities whose services are not enough for a few pages, but for their services, books containing several volumes are needed. One of them is Sheikh Hadith Maulana Amanullah, who served Islam in various ways. It was felt that constant research work should be done on his services so that people can be aware of his services, and can make a plan of action by making his life as a model for attaining the pleasure of Allah.